MIND MAP IMPLEMENTATION IN INTEGRATED NATURAL SCIENCE EDUCATION TO IMPROVE PGSD STUDENTS' CREATIVITY - Ana Fitrotun Nisa; Shanta Rezkita (JPSD (Jurnal Pendidikan Sekolah Dasar), 2020)
This study aims to determine the implementation of mind maps in Integrated Natural Science education learning in improving the Elementary School Teacher Education students' creativity, Faculty of Teacher Training and Education, UST Yogyakarta. The type of this research is a classroom action research with a model design from Kemmis and Mc Taggart. The subjects in this research were 3G class students of Integrated Natural Science of Elementary Schools course with 44 students, while the object of this research was the mind map method and students' creativity. This research was conducted in two cycles with each cycle consisting of planning, acting, observing and reflecting. Data collection techniques are using observation, questionnaires, and documentation. The data analysis technique used is descriptive analysis with the percentage criteria of creativity improvements. The results showed that the mind map method could improve the Elementary School Teacher Education students' creativity, Faculty of Teacher Training and Education, UST Yogyakarta. The creativity improvement can be seen from the average percentage in cycle 1 of 68.53% and in cycle 2 of 87.64%. This shows that the mind maps method can improve Elementary School Teacher Education students' creativity, Faculty of Teacher Training and Education, UST Yogyakarta.                                                                                   Keywords: Mind Map; Science; Creativity; Students